Procedures and services in the GAD Municipality of Ambato - Tite, Ramiro (2014)
Analysis of the procedures and services in the GAD Municipality of Ambato during the period January-June 2014. DOI: https://doi.org/10.31164/bcoyu.3.2014.554 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/554